Enuresis: modern aspects of etiology, pathogenesis, psycho-, pharmaco-, physical therapy and phytotherapy (part 2) - Shtrygol, Diana V.; Shtrygol, Sergiy Yu. (Psychiatry, Neurology and Medical Psychology, 2020)
In the second part of the review, the current state of the pharmacological, psycho-, physical therapy and phytotherapy of enuresis is analyzed in detail. An algorithm for the treatment of bedwetting, recommended by experts from the International Children’s Continence Society, based primarily on behavioral therapy, alarm-therapy (“bedwetting alarm clock”), pharmacotherapy, is considered. Methods of psychotherapy are discussed in detail: behavioral therapy, in particular the token system, as well as the differentiated application of the method of suggestion (hypnotic, "maternal suggestion", the method of "hypnosis-repose", self-hypnosis). The using of play therapy, cognitive-behavioral, family-, art therapy, and a child variant of gestalt therapy in psychotherapy of neurotic disorders in case of enuresis is substantiated. The date showing the effectiveness of alarm therapy (a lower rate of subsequent relapses and a lower risk of side effects compared with the widespread treatment with desmopressin) are given. The main targets of pharmacotherapy and the corresponding drugs are analyzed in accordance with the etiology and pathogenesis of the disease. The use of psychostimulants, tricyclic antidepressants for normalization of the sleep depth, nootropic drugs (especially calcium hopantenate) in neurosis-like enuresis, and anxiolytics and sedatives in the relatively rare neurotic form is substantiated. New approaches to pharmacotherapy are discussed, including the use of uroselective antagonists of M3-cholinergic receptors (tolterodine, solifenacin), α1-adrenoblockers, non-steroidal anti-inflammatory drugs in the off label format. A critical analysis of treatment with desmopressin is given. The features of differentiated physical therapy of enuresis (high frequency current, electrophoresis with antispasmodics, magnetic therapy, thermal procedures, electric sleep, reflex therapy, exercise therapy, biofeedback method) are considered. The analysis of traditional approaches to herbal medicine as an auxiliary method of enuresis treatment using neurotropic, anticholinergic, antispasmodic properties of plants is presented. Strategies for increasing compliance and creating a therapeutic alliance are discussed. The researches supporting the benefits of early treatment of bedwetting are analyzed.